Behavior change techniques to increase physical activity among older adults living in long-term care facilities: A systematic review - Shi, Ying; Xie, Tingting; Xie, Xiyan; Shao, Lu; Lao, Aidi; Zhang, June (Journal of health psychology, 2025)
Despite the health benefits of physical activity, many older adults living in long-term care facilities lead sedentary lifestyles and do not meet minimum physical activity recommendations. Determining the behavior change techniques (BCTs) used in physical activity interventions can help us understand the underlying mechanisms by which behavioral change is achieved. The purpose of this systematic review was to identify and evaluate BCTs in physical activity interventions for the elderly residents. Six electronic databases were searched and 15 eligible studies were retained. Nine promising BCTs associated with physical activity promotion among elderly residents were identified: credible source, social support (unspecified), goal setting (outcome), goal setting (behavior), demonstration of the behavior, instruction on how to perform a behavior, self-monitoring of behavior, self-monitoring of outcome(s) of behavior, and adding objects to the environment. Future research is encouraged to select and tailor these BCTs to the specific needs and preferences of the target population.